Pertanggungjawaban Pidana Kapal Berbendera Asing: Studi Kasus Tumpahan Minyak Akibat Kapal MV Ever Judger - Muhammad Fadli Chainurriezqy (Jurnal Hukum Lex Generalis, 2026)
Criminal liability of foreign-flagged vessels for national water pollution remains inadequately integrated between international maritime law and domestic criminal law, particularly in the context of internal waters. This research examines the MV Ever Judger oil spill in Balikpapan Bay to analyze Indonesia’s criminal jurisdiction under UNCLOS 1982 and corporate criminal liability under Indonesian positive law. Employing normative legal research with statutory and conceptual approaches, this study affirms that Indonesia holds full criminal jurisdiction based on the territorial principle and the ship-owning corporation may be held liable pursuant to the doctrine of vicarious liability and Article 116 of Law No. 32 of 2009.